Emerging Promise of Green Synthesized Metallic Nanoparticles for the Management of Neurological Disorders - Moghaddam, Zahra Esmaeili; Hamidi, Samin; Azarfarin, Maryam; Salatin, Sara (Current Pharmaceutical Design, 2025)
The management of neurological disorders is very challenging due to the presence of the blood- brain barrier (BBB) that prevents the entry of drugs into the central nervous system (CNS). The advancement of metallic nanoparticles (NPs) provides a novel direction for the treatment of neurological disorders. However, there is a significant concern regarding the toxic effects of metal NPs on biological tissues like the brain. The green synthesis strategy offers a superior alternative to the traditional methods for the development of metallic NPs. Notable metal and metal oxide NPs can be produced using various bio-reductants derived from natural sources such as plant tissues, fungi, bacteria, yeast, and alga. These biological agents play double roles as they expedite the reduction process and act as capping and stabilizing agents. In this paper, we discuss the major neurological disorders and the physical barriers limiting the transport of therapeutics to the CNS. Moreover, a special focus is given to the unique features of green synthesized metallic NPs for therapeutic purposes in various neurological disorders. The insights provided will guide future research toward better outcomes and facilitate the development of innovative treatments for neurological disorders.
Keywords: stabilizing agents